Numeracy skills for undergraduate nursing students’ clinical skill assessment: an expository analysis - Nurumal, Mohd. Said; Jamaludin, Thandar Soe Sumaiyah; Ahmad, Norfadzilah; Muhammad, Siti Aeshah @ Naznin; Mei Chan, Chong (MedWin Publishers, 2022)
Introduction: Nursing and mathematics are synonymous, particularly in clinical settings. Numeracy skills have been identified as one of the competency elements for outcome-based education in nursing. Studies have shown that undergraduate nursing students continue to perform poorly on clinically-related numeracy tasks, making errors that betray fundamental misconceptions about the underlying mathematics. These conditions can be eliminated when an effort is made and the effects can be rewarding for nursing students, nursing academics and as well as improving patient care. Aim: This study aimed to address the importance of numeracy skills for undergraduate nursing students’ clinical skill assessment. Method: This study used an expository analysis approach to address the issues of the importance of numeracy skills competency in the clinical skill assessment of undergraduate nursing students. We have analysed the current undergraduate nursing curriculum and clinical skill assessment components. Moreover, we also review the available literature related to numeracy skills competency for nursing students and newly registered nurses. Finding: Numeracy skills are one of the important elements of competencies skills that have been introduced to the current Malaysian undergraduate nursing programme. However, the achievement part of it is still questionable. Evidence has shown that new graduate nurses often lack the numeracy skills needed to enable them to do their jobs safely and effectively in the clinical setting. Among the errors done by the new graduate nurses and nursing students are drug calculation errors and which accounted for 30-40% in the clinical. Conclusion: Numeracy skills competency assessment is vital for undergraduate nursing students who have to make complex calculations and analyse the patient’s situation in their clinical setting. Improving numeracy skills for undergraduate nursing students can reduce medical errors and ultimately improve efficiency in the nursing care towards their patients.